Missing an opportunity: the embedded nature of weight management in primary care. Issue 5 (25th August 2015) - Asselin, J.; Osunlana, A. M.; Ogunleye, A. A.; Sharma, A. M.; Campbell‐Scherer, D.
Summary: The 5As Team study was designed to create, implement and evaluate a flexible intervention to improve the quality and quantity of weight management visits in primary care. The objective of this portion of the study was to explore how primary care providers incorporate weight management in their practice. 5AsT is a randomized controlled trial (RCT) on the implementation of a 6‐month 5 As Team (5AsT) intervention designed to operationalize the 5As of obesity management in primary care. Data for the qualitative portion of the study presented here included semi‐structured interviews with 29 multidisciplinary team providers and field notes of intervention sessions. Thematic analysis was undertaken. A key pattern that emerged from the data was that healthcare providers usually do not address obesity as a primary focus for a visit. Rather, obesity is embedded in a wide range of primary care encounters for other conditions. Implications were it can take extra time to discuss weight, it can be inappropriate to bring up weight as a topic, and treating risk factors and root causes of obesity have indirect benefits to patient weight management. Our findings have implications for obesity treatment approaches and tools that assume a discreet weight management visit. The embedded nature of obesity management in primary care can be harnessed to leverage multiple opportunities for asking and assessing root causes of obesity, and working longitudinally towards individual health goals.